1996
DOI: 10.1177/107155769600300207
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factors I and II Peptide and Messenger RNA Levels in Macrosomic Infants of Diabetic Pregnancies

Abstract: Cord serum IGF-II levels are elevated in diabetic pregnancies without a concomitant increase in placental IGF-II levels. This novel finding, combined with the finding that IGF-I levels are correlated with macrosomia independent of the diabetic state, contributes to our understanding of the possible mechanisms involved in fetal growth in pregnancies complicated by diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Growth-restricted infants had decreased IGF-I and increased IGFBP-I (decreasing the availability of free IGF-I) compared with a control group. Supporting this concept, Roth et al [47] have reported increased IGF-I concentrations in macrosomic infants compared with a control group. Furthermore, there was a significant correlation between cord IGF-I concentrations and birth weight (r 2 = 0.61).…”
Section: Potential Role For Growth Factors In Determining Fetal Body mentioning
confidence: 90%
“…Growth-restricted infants had decreased IGF-I and increased IGFBP-I (decreasing the availability of free IGF-I) compared with a control group. Supporting this concept, Roth et al [47] have reported increased IGF-I concentrations in macrosomic infants compared with a control group. Furthermore, there was a significant correlation between cord IGF-I concentrations and birth weight (r 2 = 0.61).…”
Section: Potential Role For Growth Factors In Determining Fetal Body mentioning
confidence: 90%
“…Physiologically, insulin as the mediator of this nutritional effect directly influences circulating IGF-I and IGF-II concentrations in the fetus [30]. Fetal hyperinsulinism due to a permanent hyperglycemia of the mother (badly controlled diabetes) induces an increase of IGF-I expression which is measurable in cord blood of these macrosomic newborns [31]. In insulin deficiency, the fetus exhibits growth retardation, muscle wastage and reduced body fat as well as significantly reduced IGF-I concentrations.…”
Section: Insulin-like Growth Factorsmentioning
confidence: 99%
“…Among the angiogenic factors vascular endothelial growth factor (VEGF), fibroblast growth factor (FGF-2), angiopoietins, placental growth factor (PlGF), tumor necrosis factor (TNFA), interleukin 8 (IL-8) and insulin-like growth factors 1 and 2 (IGF1, IGF2) have been identified, of which TNFA can as well act in an angiostatic manner [24]. Most of them are altered in maternal diabetes mellitus [25][26][27][28][29][30][31]. The effect of these factors on the early processes in angiogenesis is unclear and awaits investigation.…”
Section: The Placenta In Early Diabetic Pregnancymentioning
confidence: 99%